Freestanding 2D NiFe Metal–Organic Framework Nanosheets: Facilitating Proton Transfer via Organic Ligands for Efficient Oxygen Evolution Reaction. Issue 26 (31st May 2022) - Liu, Yizhe; Li, Xintong; Sun, Qidi; Wang, Zilong; Huang, Wei‐Hsiang; Guo, Xuyun; Fan, Zhanxi; Ye, Ruquan; Zhu, Ye; Chueh, Chu‐Chen; Chen, Chi‐Liang; Zhu, Zonglong
Abstract: The oxygen evolution reaction (OER) is crucial to electrochemical hydrogen production. However, designing and fabricating efficient electrocatalysts still remains challenging. By confinedly coordinating organic ligands with metal species in layered double hydroxides (LDHs), an innovative LDHs‐assisted approach is developed to facilely synthesize freestanding bimetallic 2D metal–organic framework nanosheets (2D MOF NSs), preserving the metallic components and activities in OER. Furthermore, the research has demonstrated that the incorporation of carboxyl organic ligands coordinated with metal atoms as proton transfer mediators endow 2D MOF NSs with efficient proton transfer during the electrochemical OHads  → Oads transition. These freestanding NiFe‐2D MOF NSs require a small overpotential of 260 mV for a current density of 10 mA cm –2 . When this strategy is applied to LDH nanosheets grown on nickel foam, the overpotential can be reduced to 221 mV. This outstanding OER activity supports the capability of multimetallic organic frameworks for the rational design of water oxidation electrocatalysts. This strategy provides a universal path to the synthesis of 2D MOF NSs that can be used as electrocatalysts directly. Abstract : A layered double hydroxides (LDHs)‐assisted method to prepare freestanding bimetallic 2D metal–organic framework (MOF) nanosheets by confinedly coordinating organic linkers with metal components in LDHs is introduced. The freestanding 2D MOFs with efficient proton transfer ability demonstrate superior activity and robust stability toward the oxygen evolution reaction.